Front Cover: The Adrenal Lipid Droplet is a New Site for Steroid Hormone Metabolism. Issue 23 (5th December 2018) - Yu, Jinhai; Zhang, Linqiang; Li, Yunhai; Zhu, Xiaotong; Xu, Shimeng; Zhou, Xiao‐Ming; Wang, Haizhen; Zhang, Hongchao; Liang, Bin; Liu, Pingsheng
Abstract : DOI:10.1002/pmic.201800136 In article number1800136, Yu et al. analyze the adrenal gland lipid droplet (LD) proteomes from human, macaque monkey, and rodent and reveal that steroidogenic enzymes are also present in abundance on LDs. The enzymes found include 3β‐hydroxysteroid dehydrogenase (HSD3B) and estradiol 17β‐dehydrogenase 11 (HSD17B11). Furthermore, the analyses demonstrate that HSD3B2 is localized on LDs. Further experiments confirm that isolated LDs from HeLa cells stably expressing HSD3B2 or from rat adrenal glands have the capacity to convert pregnenolone to progesterone. These data suggest that LDs may be important sites of steroid hormone metabolism.